2018
DOI: 10.1159/000488836
|View full text |Cite
|
Sign up to set email alerts
|

Long Intergenic Noncoding RNA 00152 Promotes Glioma Cell Proliferation and Invasion by Interacting with MiR-16

Abstract: Background/Aims: Long noncoding RNAs (lncRNAs) are a novel class of protein-noncoding transcripts that are aberrantly expressed in multiple diseases including cancers. LINC00152 has been identified as an oncogene involved in many kinds of cancer; however, its expression pattern and function in human glioma remain unclear. Methods: Quantitative real-time polymerase chain reaction was carried out to measure LINC00152 expression in human glioma cell lines and tissues. CCK-8 and EdU assays were performed to assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…Notably, long intergenic non-coding RNA 00152 (LINC00152) has been reported to be increased in numerous types of cancer, including glioblastoma, ovarian cancer, urothelial bladder carcinoma and breast cancer (21)(22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, long intergenic non-coding RNA 00152 (LINC00152) has been reported to be increased in numerous types of cancer, including glioblastoma, ovarian cancer, urothelial bladder carcinoma and breast cancer (21)(22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression of lncRNA DQ786243 predicts poor prognosis and contributes to the progression of hepatocellular carcinoma (HCC) (9). Cytoskeleton regulator RNA enhances glioma development via sponging microRNA (miR)-16 (10). These results support the important roles of lncRNAs in cancer.…”
Section: Introductionmentioning
confidence: 74%
“…14,15,25,26 Interestingly, Peng et al reported that decreasing BCYRN1 expression attenuates the viability and motility of cervical cancer cells through targeting of miR-138. 22 Additionally, many lncRNAs, such as MALAT1, 27 MNX1-AS1, 28 LINC00152 29,30 and DANCR, 31 have been verified to act as ceRNAs that regulate the tumorigenesis and progression of gliomas. Inspired by the ceRNA regulatory network, we hypothesized that BCYRN1 may also serve as a ceRNA by directly binding to specific miRNAs.…”
Section: Discussionmentioning
confidence: 99%